God's resistance: mobilizing faith to defend immigrants - Christerson, Brad (New York University Press, 2023)
"This book explores the power of faith in mobilizing resistance to restrictive immigration policies in the US by analyzing the strategies, successes, and failures of faith-based immigrant rights organizations"--